Rethinking The Paradigm Of Islamic Banking: Integrated Of Commercial And Social Oriented - Siti Aisyah; Nurizal Ismail; Ibrahim Fahad Sulaiman; Eko Nur Cahyo; Devid Frastiawan Amir Sup (Al-Iktisab: Journal of Islamic Economic Law, 2024)
Vol 6, No 2 (2022) Page (147-168)